ANALISIS PENERAPAN STORE ATMOSPHERE DAN KUALITAS PRODUK DALAM MENINGKATKAN MINAT BELI KONSUMEN PADA CAFE MARBLE COFFEE TEMBILAHAN - Rendi Prayoga; Lie Othman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Consumer buying interest is one of the factors in increasing sales turnover in the field of marketing. Store atmosphere and product quality are one of the factors or elements in increasing consumer buying interest. This study aims to determine the application of the influence of store atmosphere and product quality in increasing consumer buying interest in cafe marble coffee tembilahan. This study uses descriptive and quantitative statistics. The population of this research is all customers of the Tembilahan marble coffee cafe. Using accidental sampling technique with a sample of 99 respondents. The data source is taken from primary data which is processed through the SPSS program. And the secondary data used are sales data and target data for the realization of the marble coffe tembilahan café. This study uses simple and multiple linear regression analysis methods, through validity tests and reliability tests. In this study the results obtained were that store atmosphere (X1) had a significant effect on consumer buying interest (Y), product quality (X2) had a significant effect on consumer buying interest (Y) and store atmosphere (X1) and product quality (X2) had a significant effect on consumer buying interest (Y) at the Tembilahan Marble Coffe Café Keywords: Store Atmosphere, Product Quality And Consumer Buying Interest.